Остеоінтеграція дентальних імплантатів з різними типами поверхні - Міщенко, Олег Миколайович; Солодовник, О. В.; Олешко, О. М.; Mishchenko, O. M.; Solodovnik, O.; Oleshko, O. (My University, 2020)
Незважаючи на чисельні модифікації поверхні імплантатів, використання кальцій-фосфатних складових є найбільш вживаною методикою через подібність за складом до екстрацелюлярного матриксу кістки. Саме наявність іонів кальцію та фосфору, а також оптимальні розміри структур поверхностей, здатні збільшити абсорбцію білків та адгезію клітин остеобластичного диферону на поверхні імплантату. Проте залишається багато питань щодо впливу модифікацій поверхні, можливості використання мікро- та нанорозмірних модифікацій та ефективності різних типів покриття у віддалені терміни постімплантаційного остеогенезу. Крім того, недостатньо вивчений вплив механічних параметрів самого імплантата в поєднані з різними типами модифікації поверхні. Мета роботи — вивчення за допомогою електронної мікроскопії механізмів остеоінтеграції в експерименті на лабораторних тваринах. Despite numerous modifications to the surface of the implants, the use of calcium-phosphate components is the most used technique because of the similarity in composition to the extracellular bone matrix. It is the presence of calcium and phosphorus ions, as well as the optimal sizes of surface structures that can increase the absorption of proteins and the adhesion of osteoblastic differential cells on the implant surface. However, many questions remain regarding the effect of the size of surface modifications, the possibility of using micro- and nanoscale modifications, and the effectiveness of various types of coatings in the long-term post-implantation osteogenesis. In addition, the influence of the mechanical parameters of the implant itself in combination with various types of surface modification has not been sufficiently studied. Objective — to study using tissue electron microscopy of tissue mechanisms of osseointegration in an experiment on laboratory animals.
Osseointegration of dental implants with various surface types
Keywords: остеоінтеграція; морфологічні аспекти інтерфейсу імплантат-кістка; імплантат; osseointegration; morphological aspects of the implant-bone interface; implant